Effect of Denonvilliers' Fascia Preservation Versus Resection During Laparoscopic Total Mesorectal Excision on Postoperative Urogenital Function of Male Rectal Cancer Patients: Initial Results of Chinese PUF-01 Randomized Clinical Trial. Issue 6 (December 2021) - Wei, Bo; Zheng, Zongheng; Fang, Jiafeng; Xiao, Jian'an; Han, Fanghai; Huang, Meijin; Xu, Qingwen; Wang, Xiaozhong; Hong, Chuyuan; Wang, Gongping; Ju, Yongle; Su, Guoqiang; et al.
Abstract : Objective: To compare the outcomes of laparoscopic total mesorectal excision (L-TME) with Denonvilliers' fascia (DVF) preservation versus resection on urogenital function of male patients with rectal cancer. Background: The protective effect of DVF during L-TME on pelvic autonomic nerves and postoperative urogenital function remains controversial. Methods: Between August 26, 2015 and July 18, 2019, 253 male patients with cT1–4 (T1–2 for anterior wall) N0–2 M0 rectal cancer from 11 institutions were enrolled, and randomly assigned to L-TME with DVF preservation (Exp-group, n = 123) or resection procedures (Con-group, n = 130). Urinary function was assessed by residual urine volume, maximal flow rate, and International Prostate Symptom Score; sexual function was assessed by 5-item version of the International Index of Erectile Function (IIEF-5) and ejaculation grading. Results: The Exp-group patients showed a lower urinary dysfunction rate (6.8% vs 25.4%, P = 0.003), higher maximal flow rate (16.25 ± 8.02 vs 12.40 ± 7.05 mL/s, P = 0.007), and lower International Prostate Symptom Score (6.55 ± 5.86 vs 8.57 ± 5.85, P = 0.026) than the Con-group patients at 2 weeks after surgery. The incidence of erectile dysfunction (IIEF-5 ⩽ 11) at 12 months after surgery was lower in the Exp-group than in the Con-group (12.5% vs 34.2%, P = 0.023); Exp-group manifested superior IIEF-5 (16.63 ± 6.28 vs 12.26 ± 6.83, P = 0.018). The incidence of ejaculation dysfunction was lower in the Exp-group than in the Con-group at 12 months after surgery (10.0% vs 29.4%, P = 0.034). Conclusions: DVF preservation during L-TME revealed protective effects on postoperative urogenital function, and could be a better choice for male rectal cancer patients with specific staging and location. Trial registration number: NCT02435758. Abstract : Supplemental Digital Content is available in the text